Economic and legal mechanism for the service enterprise operation (Nexo Revista Científica, 2021)
The article is dedicated to developing an economic and legal mechanism for the service enterprise operation. It has been determined that the components of the economic management mechanism of a service enterprise are economic and legal mechanisms that are closely interconnected. It has been revealed that the economic mechanism lies behind the economic management and determines the deep objective basis of this phenomenon. It reflects the combination of economic, organizational, and administrative levers, and methods that regulate organizational and technical, service and technological, financial and economic processes and relations for the efficient results of a business entity in the current context. It has been proved that when determining the form of a service enterprise, it is necessary to define its meaningful individuality according to the legislation and to recognize this form as the basis for classifying such subjects into types within the relevant generic concepts thereto.